1994
DOI: 10.1210/endo.135.6.7988473
|View full text |Cite
|
Sign up to set email alerts
|

C-type natriuretic peptide (CNP) in the pituitary: is CNP an autocrine regulator of gonadotropes?

Abstract: Natriuretic peptides act via receptors with intrinsic guanylate cyclase activity to stimulate cGMP production and are thought to be important regulators of neuroendocrine systems. C-Type natriuretic peptide (CNP) is of particular interest in this regard because the highest tissue concentrations of CNP occur in the anterior pituitary, where it is a highly potent stimulator of cGMP production. Here we show that pituitaries of rats and mice contain abundant CNP prohormone messenger RNA (mRNA), but no atrial natri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Immunocytochemical analysis demonstrated CNP immunoreactivity localized to gonadotroph cells. 22 Gonadotrophin-releasing hormone neuronal cell lines also express both CNP and NPR-B. 23 These data suggest a paracrine role for CNP in the regulation of gonadotrophinreleasing hormone-secreting hypothalamic neurons and gonadotrophin-releasing hormone-responsive pituitary cells and raise the possibility that CNP may influence the neuroendocrine control of reproduction.…”
Section: Discussionmentioning
confidence: 91%
“…Immunocytochemical analysis demonstrated CNP immunoreactivity localized to gonadotroph cells. 22 Gonadotrophin-releasing hormone neuronal cell lines also express both CNP and NPR-B. 23 These data suggest a paracrine role for CNP in the regulation of gonadotrophinreleasing hormone-secreting hypothalamic neurons and gonadotrophin-releasing hormone-responsive pituitary cells and raise the possibility that CNP may influence the neuroendocrine control of reproduction.…”
Section: Discussionmentioning
confidence: 91%
“…McArdle et al pointed out the effects of the three natriuretic peptides on cGMP production in pituitary cells and showed that CNP is more potent and efficacious than ANP or BNP in the primary culture of rat pituitary cells and in gonadotrope-derived αT3-1 cell line, a clonal gonadotrope-derived cell line (101). The same group also reported that natriuretic peptides stimulate cGMP accumulation in pituitary cells and αT3-1 cells with a rank order of potency (CNP >> BNP > ANP) suggestive of their function via GC-B receptors (102). CNP acts via GC-B receptors to paracrine and/or autocrine effects, and CNP is located in gonadotropes.…”
Section: Hypothalamus-pituitary Systemmentioning
confidence: 93%
“…It is reported that ANP and CNP inhibited [ 3 H] isatin binding to rat brain sections and isolated membrane fraction, and isatin antagonized not only NPR-A (ANP-stimulation of GC) but also NPR-C signaling. Competitive interactions between isatin and natriuretic peptides and their receptors give a possible explanation for (99)(100) GC A GC B >> > (101)(102) cGMP (113)(114) hydromineral homeostasis (115)(116)(117)(118) extra follicular cell granulosa cell (127) testosteron synthesis (107)(108) Leydig cell function (106,109) (119)(120)(121) ovary testis adrenal sodium and water homeostasis (105) LH induced progesterone secretion (122,(125)(126) Fig . 3.…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…In animal models, the regulation of CNP depends on a variety of influencing factors such as glucocorticoids, thyroid hormones, vasoactive peptides, and catabolic state (Igaki et al 1998;Jaszberenyi et al 1998;McArdle et al 1994;Nishimura et al 1998;Prickett et al 2007), but very little is known about regulatory mechanisms in states of critical illness in humans. Using correlation Diet andNutrition in Critical Care DOI 10.1007/978-1-4614-8503-2_24-1 # Springer Science+Business Media New York 2014 analyses, our study revealed significant associations between NT-proCNP and established laboratory biomarkers reflecting inflammation and organ function in medical ICU patients.…”
Section: Applications Of Serum Nt-procnp To Critical or Intensive Carementioning
confidence: 99%